2005
DOI: 10.1038/sj.bmt.1705024
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of relapsed acute lymphoblastic leukemia after allogeneic bone marrow transplantation with chemotherapy followed by G-CSF-primed donor leukocyte infusion: a prospective study

Abstract: Summary:Donor leukocyte infusion (DLI) alone has very limited efficacy for patients with acute lymphoblastic leukemia (ALL) who have relapsed after allogeneic bone marrow transplantation (BMT). We, therefore, prospectively tested the efficacy of cytoreductive chemotherapy (intermediate-dose cytarabine þ idarubicin þ etoposide) followed immediately by G-CSF-primed DLI (Chemo-DLI) in 10 relapsed ALL patients after allogeneic BMT. Seven achieved complete remission (CR) at a median of 25 days (19-73 days) after DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…26 On the other hand, Bader et al reported that the administration of a low-dose of donor lymphocyte infusion in 31 children with mixed chimerism post-HSCT resulted in better outcomes. [27][28][29] In the present study, 16 patients had acute GVHD grade II-IV and no statistical differences were found in terms of event-free survival. Two of ten MRD-positive patients who are currently alive have chronic GVHD.…”
Section: Discussionmentioning
confidence: 78%
“…26 On the other hand, Bader et al reported that the administration of a low-dose of donor lymphocyte infusion in 31 children with mixed chimerism post-HSCT resulted in better outcomes. [27][28][29] In the present study, 16 patients had acute GVHD grade II-IV and no statistical differences were found in terms of event-free survival. Two of ten MRD-positive patients who are currently alive have chronic GVHD.…”
Section: Discussionmentioning
confidence: 78%
“…8 The other major cause of morbidity and mortality is relapse, occurring in more than 30% of transplant recipients with B-cell acute lymphoblastic leukemia (B-ALL), 9-12 with few appealing therapeutic options and less than 10% long-term survival. 13,14 Although donor lymphocyte infusions can be used after HSC transplantation to treat both viral infections and leukemia relapse, these are associated with potentially life-threatening GVHD, 15 have a low success rate in relapsed B-ALL, 15,16 and are unavailable for CB transplant recipients. An alternative for viral infections is the adoptive transfer of cytotoxic T lymphocytes (CTLs) directed to CMV, 17,18 EBV, 19,20 and, more recently, AdV, 21,22 which can rapidly reconstitute antiviral immunity after HSC transplantation without causing GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Despite initial reports of success using DLI to treat relapsed ALL, 66 the success of this intervention has been a disappointment and remains largely anecdotal. 63,[67][68][69] This may be somewhat surprising, as in ALL there are a number of published studies [70][71][72] showing a strong association between a decrease in disease relapse in ALL patients who develop GvHD, suggesting that there is a strong GvL effect. A possible explanation for Table 1 The outcome reported in recent studies following donor leucocyte infusions for patients relapsing after an allograft 65 16 AML 16 31% (2 years) Kolb (1998) 58 43 ALL Unk B0 (2 years) Collins et al (2000) 73 44 ALL 28 13% (3 years) Choi et al (2005) 69 10 ALL 10 2/10…”
Section: Donor Leucocyte Infusionsmentioning
confidence: 94%